Social Learning Through Children’s Literature: A Study of The Conch Bearer by Chitra Banerjee Divakaruni (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India is prosperous enough in its cultural and traditional realm. Writers have always been inclined to explore these enlightened phenomena to magnify the cultural and social values in their readers. But as the nation is making scientific and technical progress, it is lacking in its cultural, social and moral values. Modern generation is the severe victim of this blind race of development. They are lingering between the tradition and modernity. So there is a dire need to introduce our tradition and culture to young generation to produce ethical values and children’s literature has always been preoccupied with this thought. The present novel is also a powerful attempt of the author to inject the moral values, compassion, love, goodness, honesty etc. in youngsters through a story of two children, Anand and Nisha. Abhaydatta, their companion and guide, brings out the importance of the great Indian culture, its values and introduces them to the magical world of the Silver Valley. Anand encounters Surabhanu, the evil force in his journey to return the Conch to its rightful place and emerges out as victorious warrior. Anand’s learning from the outer world serves to enhance his understanding of his inner capabilities and encouraging him to become a good human being.